Ancestral Lineages of Arbuscular Mycorrhizal Fungi (Glomales) - Redecker, Dirk; Morton, Joseph B.; Bruns, Thomas D. (Molecular phylogenetics and evolution, 2000)
Using new and existing 18S rRNA sequence data, we show that at least five species of glomalean fungi lie outside the previously defined families and diverged very early in the evolution of that group. These five fungi would have been missed by many previous ecological studies because their sequences are not well matched to available taxon-specific primers and they do not stain well with the standard reagents used for morphological analysis. Based upon spore morphology, these species are currently assigned to Glomus and Acaulospora, and two of the species are dimorphic, exhibiting spore stages of both genera. This suggests that dimorphic spores are the ancestral state for the order and that one or the other morphology was lost in various lineages. Our analyses also show that Geosiphon pyriforme, a symbiont with cyanobacteria, is not necessarily a sister group of the Glomales; instead, it may be derived from mycorrhizal ancestors.